A Jigsaw Puzzle with No Given Solution: The Financial Crisis, Trust, Loyalty and Fair-play. (December 2014) - Ericsson, Ulf; Augustinsson, Sören; Pettersson, Pär
Based on one-to-one interviews and focus group interviews with management representatives, trade union representatives, and blue- and white-collar workers this article investigates how the global financial crisis was handled in Swedish industry. In the light of the crisis agreement signed between trade union IF Metall and company representatives how can the implementation of the agreement be described? How were these new conditions interpreted and how were they experienced? Three conceptual themes emerged, trust, loyalty, and principle of fair-play. Large differences were shown that were related to attitudes towards blue- and white-collar workers, recognition of work, and the size of the town.